Structure and DNA-binding properties of the Bacillus subtilis SpoIIIE DNA translocase revealed by single-molecule and electron microscopies - Cattoni, Diego I. (Oxford University Press, 2014)
SpoIIIE/FtsK are a family of ring-shaped, membrane-anchored, ATP-fuelled motors required to segregate DNA across bacterial membranes. This process is directional and requires that SpoIIIE/FtsK recognize highly skewed octameric sequences (SRS/KOPS for SpoIIIE/FtsK) distributed along the chromosome. Two models have been proposed to explain the mechanism by which SpoIIIE/FtsK interact with DNA. The loading model proposes that SpoIIIE/FtsK oligomerize exclusively on SpoIIIE recognition sequence/orienting polar sequences (SRS/KOPS) to accomplish directional DNA translocation, whereas the target search and activation mechanism proposes that pre-assembled SpoIIIE/FtsK hexamers bind to non-specific DNA, reach SRS/KOPS by diffusion/3d hopping and activate at SRS/KOPS. Here, we employ single-molecule total internal reflection imaging, atomic force and electron microscopies and ensemble biochemical methods to test these predictions and obtain further insight into the SpoIIIE–DNA mechanism of interaction. First, we find that SpoIIIE binds DNA as a homo-hexamer with neither ATP binding nor hydrolysis affecting the binding mechanism or affinity. Second, we show that hexameric SpoIIIE directly binds to double-stranded DNA without requiring the presence of SRS or free DNA ends. Finally, we find that SpoIIIE hexamers can show open and closed conformations in solution, with open-ring conformations most likely resembling a state poised to load to non-specific, double-stranded DNA. These results suggest how SpoIIIE and related ring-shaped motors may be split open to bind topologically closed DNA.